THE ADVANTAGES OF YOUTUBE TO ENHANCE STUDENT’S VOCABULARY IN MECHANICAL ENGINEERING CLASSROOM - Syaefani Arif Romadhon; M. Taufik Qurohman (Universitas Wiralodra, 2017)
Most of Mechanical Engineering students have very low interest and motivation towards English even they regard English as huge obstacle. Besides that, it is the lack of module or material of English especially for mechanical engineering. Because of this problem, English teaching in this class needs the materials or methods which is suitable for those students therefore the student learning experience is more interesting and challenging. This is the main reason why lecturers of vocational colleges especially for mechanical engineering department is expected to always explore more motivative teaching resources, although there are many handbooks or modules include CDs. In order to learn more varied, lecturers can use English material for this department that can be taken or downloaded from Youtube. So that the students can understand and improve their English vocabulary competence related to mechanical terms. This study analyzes the effects of using material taken from Youtube in the mechanical department. Using Class Action Research consist of two cycles with stages of planning, action, observation, and reflection. Both cycles use the application of learning models by Teaching English for ESP assisted by Youtube. The result of research shows that the improvement of problem solving ability in English which is very significant that is 85,21% from 30 studenst get value ≥70 according to required minimum value.